ANA DİLİ, EDİNİMİ, ÖNEMİ VE GELİŞTİRİLMESİ - Çavuşoğlu, Ali (Fırat University, 2006)
lt can be said that the language is the nation; so if you have a language it means you belong to a nation. It is the language that transforms all valuables to generations. Looking at it at this point ofview in this papper firstly the definition of roother language will be given. Then as it is thought that the factors of geneti es lay down in the hasement of roother language in this context the acquisition oflanguage will be taken in hand. Then the importance of roother language will be stated and about the improvement oflanguage some important opiniohs will be set.
Keywords: Religious Studies; Din Araştırmaları